Comparison of knee kinematics during Single Leg Squat among physically active females with and without Dynamic Knee Valgus - Pentaya, Veenothini (2020)
Single Leg Squat (SLS) is a commonly used clinical assessment of lower limb function and a common motion in sports (i.e., running, landing from jumps, stepping) and daily activity (i.e., gait). SLS is used to evaluate Dynamic Knee Valgus (DKV) which can be applied to identify a potential risk factor for injury, a predictor for recovery and an outcome measure of rehabilitation. Moreover, females showed greater risks of knee injury compared to males due to DKV. Many clinical biomechanical tests such as drop-jump, star excursion balance, functional movement screen (FMS) and SLS tests were proposed to assess the risk of lower limb injuries. Hence, by studying the differences of knee mechanics during SLS among physically active females with and without excessive DKV, we may identify important biomechanical factors which could be trained to reduce risks of lower limb injury. This current study evaluated the knee kinematics during SLS at squat depth of 45 ̊ and 60 ̊ among physically active females (i.e., runner, volleyball and netball) with or without DKV. Thirty participants went through the Drop Vertical Jump (DVJ) screening test to confirm their eligibility to participate in the study. The two-dimensional (2D) frontal plane projection angle (FPPA) of the knee joint of dominant leg was evaluated from this screening test. This was done to observe the presence of excessive DVJ. The normal value of FPPA for females during DVJ test is from the range of 7 ̊ - 13 ̊. From the screening test, 12 participants were within the normal range of knee FPPA (i.e., Group non-DKV) and 12 participants had exceeded the normal range of knee FPPA during DVJ screening test (i.e., Group DKV). Six participants were excluded from this study due to not meeting the inclusion criteria of having knee FPPA value within 7 ̊ - 13 ̊ . The knee FPPA for these six participants were lesser than 7° (i.e., varus knee). Hence the total number of study participants are N=24. The two groups were compared and analysed using Independent T-Test. Independent T-Test was used to know if there were any significant differences across the depths of the squat and groups. Based on the test, there were no significant differences in the knee frontal plane angle during single leg squat at 45 ̊and 60 ̊ knee flexion for dominant and non-dominant legs among physically active females with and without excessive DKV. By performing these tests, two-dimensional (2D) kinematic analysis of knee FFPA may help coaches and other professionals to detect asymmetries between dominant and non-dominant limbs, and to develop training programs with the goal of reducing overall lower extremity injury risk.